(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
One of a company’s greatest assets is its workforce, and that asset appreciates in value overtime rather than depreciating. When a nation and its people can triumph in the face of overwhelmingodds, it’s clear that the health and prosperity of a business or financial institution is a direct reflection ofthe competence, skill, and effort of its employees. In this paper, the authors analyse the current state ofbank employee retention schemes and policies and discuss the need to enhance these programs.